2015
DOI: 10.3844/ojbsci.2015.260.267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity, pH, Light Intensity on Growth and Lipid Production of Microalgae for Bioenergy Application

Abstract: The crisis of energy producing molecules (fuels) is expected to increase in future, which is currently produced from crude mineral oil. Biodiesel is most reliable, non-toxic, biocompatible liquid fuel that can replace the existing unsustainable sources of energy. Among all the known sources, microalgae display high potential for the production of biodiesel owing to their numerous benefits like higher biomass productivities than plants, no agricultural land requirement, cultivation in waste water and accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…The decrease in chlorophyll content is associated with low microalgae activity and the low removal of nutrients from wastewater. Rai et al (2015) revealed that the maximum production of the biomass was recorded at pH 7 (1.3 g L -1…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhouse mentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in chlorophyll content is associated with low microalgae activity and the low removal of nutrients from wastewater. Rai et al (2015) revealed that the maximum production of the biomass was recorded at pH 7 (1.3 g L -1…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhouse mentioning
confidence: 99%
“…Microalgae use carbon at low light intensity to synthesise amino acids, whereas under saturated light, the microalgae cells produce sugars, lipids, and starch (Pérez-Pazos and Fernández-Izquierdo 2011). Rai et al (2015) estimated biomass and lipid production under different light and dark periods. The study revealed that the maximum biomass (0.54 g/L) and lipid yield (0.079 g/L) were recorded when microalgae were exposed to light for 24 h, whereas the minimum production amounted to 0.25 and 0.04 g/L for biomass and lipids, respectively, with 8 h of incubation under light.…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhouse mentioning
confidence: 99%
“…The main role of sodium chloride in algal media may be oxidative stress leading to increment in the triacylglycerol content [28][29][30] and/or changes in lipid amount and composition [27]. The type and concentration of salts are strain-dependent [31].…”
Section: Discussionmentioning
confidence: 99%
“…exposed to green light had an adverse effect on lipid production in comparison with white, yellow, and red light conditions. In this case, the highest cell growth and lipid production (13.10% of its biomass) was under red light (Rai et al ). Kim et al () demonstrated that Scenedesmus sp.…”
Section: Physicochemical Factors: Lightmentioning
confidence: 99%
“…Moreover, Chlorella sp. showed a higher biomass production under initial pH 7 and the maximum lipid production was found at initial pH 8, comprising 23% of its biomass (Rai et al ).…”
Section: Physicochemical Factors: Culture Phmentioning
confidence: 99%